Pengaruh Model Project Based Learning (PjBL) Terhadap Keterampilan Menulis Teks Prosedur Siswa Kelas IV SDN 5 Rasau Jaya - Nurul Hidayatul Jannah; Yunika Afryaningsih; Nurhaidah, Nurhaidah (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This study aims to determine the effect of the Project Based Learning model on the writing skills of procedural texts of grade IV students of SDN 5 Rasau Jaya. The research method used is a quantitative method with the design used, namely One-Group Pretest-Posttest Design. The independent variable (X) in this study is the Project Based Learning model, while the dependent variable (Y) is the skill of writing procedure texts. The population included in this study is grade IV students at Sekolah SD Negeri 5 Rasau Jaya. The sample in this study was class IV B students totaling 19 people, consisting of 12 male students and 7 female students. The technique used to determine the class for this study is purposive sampling or purposeful samples. The data collection instruments used in this study were observation sheets and procedure text writing skills assessment sheets. Based on the results of data analysis, it was found that the difference in the average pretest score in this study was 64.14 while the average posttest score was 72,68. Hypothesis testing using the Wilcoxon Test, because based on the results of the Normality Test the data obtained are abnormally distributed. The result of the Wilcoxon Test is 0.00 which means that the significant level states that the is accepted. The results showed that there was an influence of the PjBL model on the skill of writing procedure texts.This study aims to determine the effect of the Project Based Learning model on the writing skills of procedural texts of grade IV students of SDN 5 Rasau Jaya. The research method used is a quantitative method with the design used, namely One-Group Pretest-Posttest Design. The independent variable (X) in this study is the Project Based Learning model, while the dependent variable (Y) is the skill of writing procedure texts. The population included in this study is grade IV students at Sekolah SD Negeri 5 Rasau Jaya. The sample in this study was class IV B students totaling 19 people, consisting of 12 male students and 7 female students. The technique used to determine the class for this study is purposive sampling or purposeful samples. The data collection instruments used in this study were observation sheets and procedure text writing skills assessment sheets. Based on the results of data analysis, it was found that the difference in the average pretest score in this study was 64.14 while the average posttest score was 72,68. Hypothesis testing using the Wilcoxon Test, because based on the results of the Normality Test the data obtained are abnormally distributed. The result of the Wilcoxon Test is 0.00 which means that the significant level states that the is accepted. The results showed that there was an influence of the PjBL model on the skill of writing procedure texts.